2017
DOI: 10.1111/gcbb.12485
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration and turnover in soil under the energy crop Miscanthus: repeated 13C natural abundance approach and literature synthesis

Abstract: The stability and turnover of soil organic matter (SOM) are a very important but poorly understood part of carbon (C) cycling. Conversion of C 3 grassland to the C 4 energy crop Miscanthus provides an ideal opportunity to quantify medium-term SOM dynamics without disturbance (e.g., plowing), due to the natural shift in the d 13 C signature of soil C. For the first time, we used a repeated 13 C natural abundance approach to measure C turnover in a loamy Gleyic Cambisol after 9 and 21 years of Miscanthus cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 47 publications
5
52
1
Order By: Relevance
“…There was also no difference between carbon stocks at the two sampling points (T 6 and T 12 ) suggesting a reasonably stable carbon state. However, this is in contrast to Zang et al () where soil organic matter increased between sampling occasions (9 and 21 years after Miscanthus planting). This difference may be as a result of different soil pH and nutrient levels, or the slightly cooler (annual average air temperature 6.7°C vs. 10.4°C) and wetter (annual average precipitation 1,074 mm vs. 654 mm) climate in this study, which could all influence Miscanthus ‐derived carbon (Zimmermann et al, ).…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…There was also no difference between carbon stocks at the two sampling points (T 6 and T 12 ) suggesting a reasonably stable carbon state. However, this is in contrast to Zang et al () where soil organic matter increased between sampling occasions (9 and 21 years after Miscanthus planting). This difference may be as a result of different soil pH and nutrient levels, or the slightly cooler (annual average air temperature 6.7°C vs. 10.4°C) and wetter (annual average precipitation 1,074 mm vs. 654 mm) climate in this study, which could all influence Miscanthus ‐derived carbon (Zimmermann et al, ).…”
Section: Discussioncontrasting
confidence: 88%
“…In this new analysis, unlike Zatta et al (), we did find a reduction in soil carbon stock at T 6 compared to T 0 but the breakdown by hybrid confirmed that the difference was only significant for a single hybrid (at T 6 and T 12 , Figure ). The overall reduction in carbon from T 0 to T 12 , of 8 Mg/ha, is within the range +4 to −9 Mg/ha reported in other grassland to Miscanthus field‐based studies (Clifton‐Brown et al, ; Schneckenberger & Kuzyakov, ; Zang et al, ; Zimmermann et al, ). There was also no difference between carbon stocks at the two sampling points (T 6 and T 12 ) suggesting a reasonably stable carbon state.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…After this period, the new equilibrium between the plant C input, organic C stocks in soil and CO 2 losses is nearly reached and no further CO 2 losses from SOC are expected, at least until new major land‐use changes. Furthermore, in contrast to SOC pools with a comparatively short turnover rate of years to decades (Hsieh, ; Neff et al., ; Zang et al., ), the long turnover rate of SIC (ca. 85,000 year – without anthropogenic impact) (Schlesinger, ) makes CaCO 3 dissolution due to acidity induced by N fertilization, a unidirectional source of CO 2 efflux during human history.…”
Section: Discussionmentioning
confidence: 99%